Maternal Age Relationship With Abortion In Genesis Hospital Rokan Hulu - -, ELVIRAJUNITA (Jurnal Martenity and Neonatal, 2013)
Abortion is a threat or spending the products of conception before the fetus can survive outside the womb. As the limit is less than 20 weeks gestation or fetal weight less than 500 grams. known incidence of clinical pregnancy by 15% - 25% among these pregnancies had complications of bleeding in the first trimester, 50% of these experienced abortion. Hospital incidence of abortion is higher due to receive a referral. In hospitals Rokan Hulu, there were 123 cases of abortion